Synaptic Tau Seeding Precedes Tau Pathology in Human Alzheimer's Disease Brain - DeVos, Sarah L.; Corjuc, Bianca T.; Oakley, Derek H.; Nobuhara, Chloe K.; Bannon, Riley N.; Chase, Alison; Commins, Caitlin; Gonzalez, Jose A.; Dooley, Patrick M.; Frosch, Matthew P.; Hyman, Bradley T. (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) is defined by the presence of intraneuronal neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau aggregates and extracellular amyloid-beta plaques. The presence and spread of tau pathology through the brain is classified by Braak stages and thought to correlate to the progression of AD. Several in vitro and in vivo studies have examined tau pathology moving from one neuron to the next, suggesting a “prion-like” spread of tau aggregates may be an underlying cause of Braak tau staging in AD. Using the HEK293 TauRD-P301S-CFP/YFP expressing biosensor cells as a highly sensitive and specific tool to identify the presence of seed competent aggregated tau in brain lysate – ie., tau aggregates that are capable of recruiting and misfolding monomeric tau – , we detected substantial tau seeding levels in the entorhinal cortex from human cases with only very rare NFTs, suggesting that soluble tau aggregates can exist prior to the development of overt tau pathology. We next looked at tau seeding levels in human brains of varying Braak stages along six regions of the Braak Tau Pathway. Tau seeding levels were detected not only in the brain regions impacted by pathology, but also in the subsequent non-pathology containing region along the Braak pathway. These data imply that pathogenic tau aggregates precede overt tau pathology in a manner that is consistent with transneuronal spread of tau aggregates. We then detected tau seeding in frontal white matter tracts and the optic nerve, two brain regions comprised of axons that contain little to no neuronal cell bodies, implying that tau aggregates can indeed traverse along axons. Finally, we isolated cytosolic and synaptosome fractions along the Braak Tau Pathway from brains of varying Braak stages. Phosphorylated and seed competent tau was significantly enriched in the synaptic fraction of brain regions that did not have extensive cellular tau pathology, further suggesting that aggregated tau seeds move through the human brain along synaptically connected neurons. Together, these data provide further evidence that the spread of tau aggregates through the human brain along synaptically connected networks results in the pathogenesis of human AD.